Comparison of the Effects of Solifenacin Succinate for the Treatment of Overactive Bladder with Extended Release Tolterodine (Bangladesh Journal of Urology, 2020)
Objective: To compare the therapeutic effects of solifenacin succinate with extendedrelease tolterodine for the treatment of overactive bladder (OAB) in Bangladeshi patients.Methods: A prospective, randomized, single-blind, two-arm, parallel-group, clinicaltrial was conducted in the department of Urology, Bangabandhu Sheikh Mujib MedicalUniversity (BSMMU), Dhaka from January 2013 to June 2014. A total of 65 patientswith OAB were treated with solifenacin succinate 5 mg (experimental group, n=33)and extended release tolterodine 4 mg (control group, n=32), both at night daily for 12weeks. Efficacy and safety variables were assessed and compared with baseline and at 12weeks treatment in between the two groups.Results: At week 12, solifenacin succinate and extended release tolterodine demonstratedreduction in the mean number of micturition (50% vs. 51%), urgency (87% vs. 73%),urge incontinence (89% vs. 71%), nocturia (89% vs. 74%), usage of pads (90% vs.71%) per 24 hours. There was increased in the mean voided volume of each micturitionin both the groups without any difference in between them. The incidence of major adverseevents were dry mouth (15.2% vs. 9.4%), constipation (9.1% vs. 15.6%), and blurredvision (6.1% vs. 3.1%) respectively.Conclusions: Solifenacin succinate had greater efficacy to extended release tolterodine intreating overactive bladder. There were no significant treatment difference between the twogroups in decreasing the number of micturition and increasing the voided volume of eachmicturition and the incidence of major adverse events. All the adverse effects were mild andtransient in nature and discontinuation of medication due to adverse effects were low.Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.76-81